RANCANG BANGUN SISTEM MONITORING PERTANIAN HIDROPONIK BERBASIS IoT DAN APLIKASI MOBILE (HYDROTECH) - I Putu Prasna Mahardika; Putu Pande Deva Ryana Putra; Duman Care Khrisne; I Made Arsa Suyadnya (Program Studi Teknik Elektro UNUD, 2025)
Urban agricultural land conversion encourages the use of hydroponic systems. However, people's busy lives make it difficult to monitor the nutrition and environment of hydroponic plants. This study developed a monitoring system called Hydrotech, an IoT-based hydroponic monitoring system with an ESP32 microcontroller and pH, TDS, temperature (DS18B20), and water level sensors. Data from the sensors is sent to Firebase and displayed through a mobile application. The method used is an experiment and literature study. Testing was carried out by planting lettuce using the Hydrotech system to evaluate its performance. Primary data was obtained from device testing which includes data from research on the sensors used, while secondary data was obtained from previous research sensor data as a comparison with the current study. The results of this study indicate that the four sensors used, namely the pH, TDS, water level, and temperature DS18B20 sensors, can function properly. Hydrotech is also equipped with an Android application to display sensor data in real time and present historical data for each sensor used for further analysis on hydroponic plants. The Hydrotech application is also filled with a planting calendar as a reminder of planting and harvesting times for hydroponic plants. This Hydrotech monitoring system helps city residents manage hydroponics optimally and efficiently in terms of both energy and time.